Jimmy's Archive - Deakin, Robert; Watters, James (Journal of Anthropological Films, 2025)
‘50 years ago today they landed on the moon... and I'm still waiting for that future’. Jimmy's Archive provides an intimate portrait of home, place and aging in a rapidly changing urban landscape. It also contributes to practices of multi-modal anthropology in which collaborative media production actively involves interlocutors in shaping the direction and products of research. While the editing in the film was done by Robert Deakin (interspersed by collaborative screenings and feedback sessions), the ‘on set’ direction saw Jimmy improvising on camera and Robert filming with minimal intervention. As Jimmy delves into his collections of memorabilia, the film’s narrative unfolds through a combination of agency and serendipity.